Self-Compassion and Predictors of Criminality. Issue 5 (27th May 2016) - Morley, Richard M.; Terranova, Victoria A.; Cunningham, Shannon N.; Kraft, Guliz
ABSTRACT: The main focus of this article is to conduct an exploratory investigation of self-compassion, a positive indicator of mental health, as a predictor of violence and criminality within a sample of prisoners. Correlation and regression analyses were used to explore the relationship that self-compassion has with self-control, self-esteem, and social connectedness. Associations between self-compassion and the subscales of self-control were also examined. Results from both correlational analysis and regression indicate that self-compassion is correlated with all 3 variables. Correlations revealed that self-compassion was related to all 6 subscales of self-control. Regression, however, revealed that impulsivity was the only predictor of self-compassion. Further analysis revealed problems with multicollinearity. Implications and limitations of these results are discussed.